PENERAPAN MODEL PEMBELAJARAN PARTNER SWITCH UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS V SD INPRES 12/79 POLEWALI KECAMATAN SIBULUE KABUPATEN BONE - Sudirman, Sudirman; Alfathayat, A. Aldin; Kadir, Abd. (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
Abstract: This research is classroom action research which aims to improve the social studies learning outcomes of fifth grade students at SD Inpres 12/79 Polewali through the application of the Partner Switch learning model. The subjects of this research were 17 class V students. The research design is cyclical or recyclable research with four stages, namely, planning, implementing actions, observing and reflecting. Data collection techniques are observation and tests. The data analysis technique is descriptive qualitative. The results of the research show the implementation of the Partner Witch learning model. The results of the teacher and student observation format in cycle I reached the adequate category and in cycle II reached the good category. From the completeness value, student learning outcomes in cycle I were 64.7% or sufficient category and experienced an increase in the learning completeness score in cycle II, namely 76.47% or good category and met the predetermined success indicators, namely 74%. The conclusion of this research is that the application of the Partner Switch learning model can improve social studies learning outcomes for fifth grade students at SD Inpres 12/79 Polewali. Keywords: Learning Model, Partner Switch, Learning OutcomesAbstrak: Penelitian ini adalah penelitian tindakan kelas yang bertujuan untuk meningkatkan hasil belajar IPS siswa kelas V SD Inpres 12/79 Polewali melalui penerapan model pembelajaran Partner Switch. Subjek penelitian ini adalah siswa kelas V sebanyak 17 orang. Desain penelitian adalah penelitian bersiklus atau berdaur ulang dengan empat tahapan yaitu, perencanaan, pelaksanaan tindakan, observasi dan refleksi. Teknik pengumpulan data yaitu observasi dan tes. Teknik analisis data yaitu kualitatif deskriptif. Hasil penelitian menunjukkan keterlaksanaan penerapan model pembelajaran Partner witch diperoleh hasil format observasi guru dan siswa pada siklus I mencapai kategori cukup dan pada siklus II mencapai kategori baik. Dari nilai ketuntasan hasil belajar siswa pada siklus I yaitu 64.7% atau kategori cukup dan mengalami peningkatan nilai ketuntasan belajar pada siklus II yaitu 76.47% atau kategori baik dan memenuhi indikator keberhasilan yang telah ditentukan yaitu 74%. Kesimpulan dari penelitian ini adalah penerapan model pembelajaran Partner Switch dapat meningkatkan hasil belajar IPS siswa kelas V SD Inpres 12/79 Polewali. Kata Kunci: Model Pembelajaran, Partner Switch, Hasil Belajar